Strategic Management of Superior School - Nur Ilmiyati; Muhiri; Supriyatno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to describe and analyze the management strategies implemented by Public High School 1 Ciamis in realizing the efforts of excellent schools based on David Hunger's theory. By applying this theory, researcher emphasizes the importance of environmental analysis based on science and technology as the basis for the strategic formulation or planning of educational institutions. This study uses a qualitative approach with a descriptive analysis method. The results of the study are: 1) Public High School 1 Ciamis has carried out environmental analysis activities using a SWOT analysis. 2) Judging from the vision, mission, strategy and policy, strategy formulation has not focused on objectives. 3) Implementing the strategy in an effective manner, which is meant to be based on the implementation form program and the budget has been implemented in accordance with the procedure. 4) Evaluation and control of strategies has been implemented and carried out consistently, so that the results can show weaknesses in implementing the right strategy. The conclusion of this study is that schools implement four aspects of strategic management but are not yet optimal.